The statistical generalization of load’s effect on the microwaves device characteristics - Andrusenko, Evhen; Bozhenko, Karina; Zadvornuy, Andriy (Видавництво Львівської політехніки, 2010)
In this article we consider the loads parameter on a microwave device.
Keywords: loads parameters; extended set